Perancangan Strategi Implementasi Agile Governance Pada Organisasi Perangkat Daerah (OPD) - Ridwan, Ridwan; Susanti, Lusi; Zadry, Hilma Raimona; Meilani, Difana (Jurnal Media Teknik dan Sistem Industri, 2025)
ImplementingAgile Governance in Regional Government Organization (RGO) is crucial for improving the efficiency and effectiveness of public services. However, its implementation still faces various challenges such as rigid and slow bureaucracy, lack of cross-functional collaboration, suboptimal utilization of digital technology, and human resources who are not accustomed to Agile work patterns. This research is designed to develop implementation strategies forAgile Governance at Regional Government Organization (RGO). The aim is to accelerate the transformation towards a moreAgile Governance in Regional Government Organization (RGO). The research methodology adopts the MEAD (Macroergonomics Analysis and Design) macroergonomics approach that integrates human factors, technology, and work organization. In evaluating the current conditions and the importance of performance indicators, a survey was conducted using a questionnaire validated by the Content Validity Index (CVI) and analyzed using Importance-Performance Analysis (IPA). The first priority results will be used to design strategies and Key Performance Indicators for each of the proposed strategies. The research findings indicate a gap between the current conditions and the importance levels of Agile Governance performance aspects. IPA identified several priority areas that require improvement, including career development and training, risk management, transparency, job suitability, adequacy of work facilities and employee welfare. Based on these findings, strategies and Key Performance Indicators (KPIs) were formulated to enhance the implementation of Agile Governance in Regional Government Organization (RGO). ImplementasiAgile Governance pada Organisasi Perangkat Daerah (OPD) menjadi penting untuk meningkatkan efisiensi dan efektivitas layanan publik. Namun, penerapannya masih menghadapi berbagai tantangan seperti birokrasi yang kaku dan lambat, kurangnya kolaborasi lintas fungsi, pemanfaatan teknologi digital yang belum optimal, serta sumber daya manusia yang belum terbiasa dengan pola kerja Agile. Penelitian ini dilakukan untuk merancang strategi implementasiAgile Governance pada Organisasi Perangkat Daerah (OPD). Tujuannya adalah mempercepat transformasi menuju tata kelola yang lebih Agile pada Organisasi Perangkat Daerah. Metodologi penelitian mengadopsi pendekatan ergonomi makro, Macroergonomics Analysis and Design (MEAD) yang mengintegrasikan antara faktor manusia, teknologi dan organisasi kerja. Dalam evaluasi kondisi saat ini dan kepentingan aspek kinerja dilakukan survei dengan kuesioner yang divalidasi menggunakan Content Validity Index (CVI) dan dianalisis menggunakan Importance-Performance Analysis (IPA). Hasil prioritas utama menjadi fokus perancangan strategi dan Key Performance Indikator (KPI) untuk masing-masing strategi yang dirancang. Hasil penelitian menunjukkan adanya kesenjangan antara kondisi saat ini dan tingkat kepentingan aspek-aspek kinerja Agile Governance. IPA mengidentifikasi beberapa area prioritas yang memerlukan perbaikan, termasuk pengembangan karir dan pelatihan, pengelolaan risiko, transparansi, kesesuaian jabatan, dan kelengkapan sarana kerja, dan kesejahteraan karyawan. Berdasarkan temuan tersebut, dirumuskan strategi dan Key Performance Indicators (KPI) untuk meningkatkan implementasi Agile Governance pada Organisasi Perangkat Daerah (OPD).